A Fig Leaf of “Green Architecture” - Bagina, Elena (project baikal, 2019)
The idea of the city’s health is usually associated with greenery. Everybody calls for parks, gardens, street landscaping, but the declarations are not consistent with the reality. Urban greenery is treated cruelly. Being considered a cure-all solution by many architects, “green architecture” is like a fig leaf, which covers the crisis of architecture.